Resistance Analysis for the Application of Flowbow on DTMB 5415 Ship - Arga Setya Andreardani; I Ketut Suastika; Baharuddin Ali; Taufiq Arif Setyanto; Mahendra Indiaryanto; Amalia Ika Wulandari; Anson Novendra Pradana (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
Flowbow is an innovation designed by Rasmussen to increase fuel efficiency by reducing wave making resistance of ship. It is claimed that Flowbow can reduce the resistance of displacement and semi-displacement hull type at Froude number (Fr) over 0.25 to 0.28. On a warship, resistance reduction can increase the patrolling endurance by reducing energy used to moving. This research comparing the hull of DTMB 5415 model, which is already using bulbous bow and the modified DTMB 5415 hull with the addition of Flowbow using CFD which is validated by EFD. The results show that the addition of a Flowbow reduces ship resistance at Fr greater than 0.249 and the resistance reduction increases as the ship speed increases. At the highest tested speed (Fr = 0.352), the total resistance reduction reaches 8.57%.